Functional characterization of circulating tumor cells (CTCs) from metastatic ER+/HER2− breast cancer reveals dependence on HER2 and FOXM1 for endocrine therapy resistance and tumor cell survival: implications for treatment of ER+/HER2− breast cancer - Roßwag, Sven; Cotarelo, Cristina L.; Pantel, Klaus; Riethdorf, Sabine; Sleeman, Jonathan P.; Schmidt, Marcus; Thaler, Sonja (Cancers, 2021)
Mechanisms of acquired endocrine resistance and late recurrence in patients with ER+/HER2− breast cancer are complex and not fully understood. Here, we evaluated mechanisms of acquired resistance in circulating tumor cells (CTCs) from an ER+/HER2− breast cancer patient who initially responded but later progressed under endocrine treatment. We found a switch from ERα-dependent to HER2-dependent and ERα-independent expression of FOXM1, which may enable disseminated ER+/HER2− cells to re-initiate tumor cell growth and metastasis formation in the presence of endocrine treatment. Our results also suggest a role for HER2 in resistance, even in ER+ breast cancer cells that have neither HER2 amplification nor activating HER2 mutations. We found that NFkB signaling sustains HER2 and FOXM1 expression in CTCs in the presence of ERα inhibitors. Inhibition of NFkB signaling blocked expression of HER2 and FOXM1 in the CTCs, and induced apoptosis. Thus, targeting of NFkB and FOXM1 might be an efficient therapeutic approach to prevent late recurrence and to treat endocrine resistance. Collectively our data show that CTCs from patients with endocrine resistance allow mechanisms of acquired endocrine resistance to be delineated, and can be used to test potential drug regimens for combatting resistance.
Gesehen am 03.08.2021